Integration of transcriptomic and metabolomic analysis of the mechanism of dietary N-carbamoylglutamate in promoting follicle development in yaks - Zhou, Jia; Yue, Shuangming; Du, Jingjing; Xue, Benchu; Wang, Lizhi; Peng, Quanhui; Zou, Huawei; Hu, Rui; Jiang, Yahui; Wang, Zhisheng; Xue, Bai (Frontiers in Veterinary Science, 2022)
Yak is the main livestock in the highlands of China. The low reproductive rate of yaks is a serious constraint on their production and utility. N-carbamylglutamate (NCG) can increase arginine synthesis in mammals and has been shown to improve reproductive performance. Twelve multiparous and simutaneous anoestrous female yaks were randomly divided into two groups, one of which was fed the basal diet (Control, n = 6), and the other was fed the basal diet supplemented with NCG at 6 g/day/yak (NCG, n = 6). All yaks were slaughtered on the 32nd day (the time predicted for the selection of the last wave of dominant follicles), and their ovarian tissues were collected and follicles were classified. NCG supplementation increased the number of large ovarian follicles (diameter > 10 mm), as well as caused significant changes in the transcriptional and metabolic levels in yak ovaries which due to the differential expression of 889 genes and 94 metabolites. Integrated analysis of the transcriptomics and metabolomics data revealed that the differentially expressed genes and differential metabolites were primarily involved in the process of energy metabolism, amino acid metabolic pathways, carbohydrate metabolic pathways, and lipid metabolic pathways. The highlighted changes were associated with amino acid synthesis and metabolism, ovarian steroid hormone synthesis, the pentose phosphate pathway, and the tricarboxylic acid cycle, suggesting that NCG supplementation may promote estrogen synthesis and help regulate follicular development by altering the pathways associated with glucose catabolism. The results present important clues for understanding the mechanisms by which NCG supplementation promotes follicular development in yaks. The findings of this study provide a basis for the development and application of NCG in optimizing animal reproduction, including yak reproductive performance, which may help optimize livestock management and uplift the pastoral economy.